1982
DOI: 10.1063/1.444111
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociative channels at 1216 Å for H2O, NH3, and CH4

Abstract: H(2S) and O(1D, 3P) yields have been measured from photolysis of H2O, NH3, and CH4 at 1216 Å. From H2O, it is confirmed that the H2+O(1D) channel occurs with a yield of 0.1, but in addition there is a yield of 0.12 for the channel giving 2H(2S)+O(3P). The remaining process is H+OH production. For NH3, the NH+2H(2S) channel accounts for at least 90% of the dissociation. For CH4, combination of our data with earlier work on H2 and CH production at 1236 Å leads to the conclusion that the two major dissociative ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 25 publications
5
89
2
Order By: Relevance
“…This is presented in the form of two separate schemes describing the quantum yields of the pathways of methane photolysis, which are shown in Table 2, both of which present scenarios that contradict previous measurements. The most striking contradiction is the yield of CH 3, which is indicated to be a significant pathway in the Lyman {x photolysis of methane, contrary to what was assumed from previous studies [Mahan and Mandal, 1962;Magee, 1963;Braun et al, 1966;Laufer and McNesby, 1968;Rebbert andAusloos, 1972/1973;Slanger and Black, 1982]. Furthermore, a Doppler-selected time-of-flight study by Wang and Liu [1998] verifies the significance of the (J1) pathway, indicating the ratio of (J1) to (J3)-(J5) at 3:1.…”
Section: Methane Product Quantum Yieldscontrasting
confidence: 41%
“…This is presented in the form of two separate schemes describing the quantum yields of the pathways of methane photolysis, which are shown in Table 2, both of which present scenarios that contradict previous measurements. The most striking contradiction is the yield of CH 3, which is indicated to be a significant pathway in the Lyman {x photolysis of methane, contrary to what was assumed from previous studies [Mahan and Mandal, 1962;Magee, 1963;Braun et al, 1966;Laufer and McNesby, 1968;Rebbert andAusloos, 1972/1973;Slanger and Black, 1982]. Furthermore, a Doppler-selected time-of-flight study by Wang and Liu [1998] verifies the significance of the (J1) pathway, indicating the ratio of (J1) to (J3)-(J5) at 3:1.…”
Section: Methane Product Quantum Yieldscontrasting
confidence: 41%
“…This channel is only 1% of the total dissociation process for photon energy lower than 8.5 eV (Stief et al 1975), but grows to be 10% at 10.2 eV (Slanger & Black 1982) in the gas phase. We consider that the direct formation of O atom, reaction (3), can proceed easily even on the surface, where dangling H atoms can bend freely, whereas it seems difficult in bulk because H 2 O is surrounded by the others in all directions.…”
Section: Photolysismentioning
confidence: 99%
“…The branching of water photodissociation into H 2 + O( 1 D), of the order of 8%-10%, has been studied in the laboratory (Slanger & Black 1982), but there are no available measurements of the resultant H 2 level populations and very little theoretical work devoted to the H 2 + O( 1 D) channel. A lone study by van Harrevelt & van Hemert (2008) found that the H 2 produced by Lyα dissociation of H 2 O, which dominates the H 2 channel in comets (Huebner et al 1992), is also vibrationally excited with the peak population in v = 3 but with even J levels strongly preferred over odd ones and a peak population at J = 18.…”
Section: Observations and Spectramentioning
confidence: 99%